Vocabulary skills and virtual tools in students of A2 Universidad Católica de Cuenca - Carmona-Chica, Liliana Maribel; Argudo-Garzón, Antonio Lenín (Revista Arbitrada Interdisciplinaria Koinonía, 2022)
The effect of the e-learning tools "Kahoot" and "Wordwall" on the learning of new vocabulary content in university students was examined. Explanatory type of experimental and control group. Data were collected through pre- and post-tests and a perception survey throughout this period. Accordingly, they were amused by the application of "Kahoot" and "Wordwall" in English class, as these platforms draw students' interest during the learning process, creating a pleasant environment for learning and teaching vocabulary effectively. In addition, they like competitive activities, so these interactive games motivate them to participate in the class.